2021
DOI: 10.1002/smll.202100287
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Gene Silencing Using Targeted Lipid Nanoparticles in Metastatic Ovarian Cancer

Abstract: Ovarian cancer is an aggressive tumor owing to its ability to metastasize from stage II onward. Herein, lipid nanoparticles (LNPs) that encapsulate combination of small interfering RNAs (siRNAs), polo‐like kinase‐1 (PLK1), and eukaryotic translation‐initiation factor 3c (eIF3c), to target different cellular pathways essential for ovarian cancer progression are generated. The LNPs are further modified with hyaluronan (tNPs) to target cluster of differentiation 44 (CD44) expressing cells. Interestingly, hyaluron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Functionalized PEG-lipids enable bioconjugation of LNPs with ligands or biomacromolecules. For example, Singh et al used DSPE-PEG-amine to conjugate hyaluronan via NHS/EDC chemistry for tumor targeting, 41 and Parhiz et al used DSPE-PEGmaleimide to conjugate antibodies via SATA-maleimide chemistry. 42 While PEG is useful for LNP stability and bioconjugation, its desorption is also critical for cell transfection.…”
Section: Peg-anchored Lipidsmentioning
confidence: 99%
“…Functionalized PEG-lipids enable bioconjugation of LNPs with ligands or biomacromolecules. For example, Singh et al used DSPE-PEG-amine to conjugate hyaluronan via NHS/EDC chemistry for tumor targeting, 41 and Parhiz et al used DSPE-PEGmaleimide to conjugate antibodies via SATA-maleimide chemistry. 42 While PEG is useful for LNP stability and bioconjugation, its desorption is also critical for cell transfection.…”
Section: Peg-anchored Lipidsmentioning
confidence: 99%
“…EIF3C was one of the subunits of EIF3, playing vital roles in translation initiation [ 29 ]. Previous studies had revealed that EIF3C was inevitable for tumor progression in many cancer types, including lung cancer, glioma, and ovarian cancer [ 30 32 ]. However, the specific role of EIF3C in prostate cancer is still elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 13 subunits of EIF3 (EIF3A to EIF3M), EIF3C is the one of the functional components [ 50 ]. EIF3C was extensively reported involved in the progression of lung cancer, glioma, breast cancer, and ovarian cancer [ 30 32 , 34 ]. However, the role of EIF3C in prostate cancer has not been discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Aptamers are short single-stranded nucleic acid sequences with more affinity and selectivity for their designed antigen than antibodies that are heat-stable and nonimmunogenic. The main polymeric ligand is HA; it targets the CD44 receptor, which is overexpressed in many cancer cells, such as ovarian cancer cells . Finally, small molecules include sugars, such as mannose against dendritic cells or folate used for cancer targeting.…”
Section: Modification Of Nanoparticle Surface To Target-specific Cell...mentioning
confidence: 99%